Urban Transport Microenterprises in Abidjan - Amakoé Adoléhoumé (World Bank, Washington, DC, 2012)
This note analyses the organization, profitability, and financing of private mass transit services in Abidjan, with an emphasis on private companies operating minibuses commonly known as "gbakas". The Abidjan case study is part of a regional study launched early in 1999 under the Urban Mobility Component of the SSATP covering four cities: Abidjan, Bamako, Harare and Nairobi. The regional study was carried out by SITRASS network (Solidarite Internationale sur les Transports et la Recherche en Afrique Subsaharienne).